Histopathological Features of Incidental Neoplasms of the Gallbladder: A Case Series with Review of Literature - Anish Chandran; Sudha Sharma; Rajni Kaushik; Shailendra Kaushik (Archives of Medicine and Health Sciences, 2024)
Gallbladder (GB) neoplasms, although rare, are the most common group of malignant neoplasms of the biliary system and can be missed preoperatively as well as on gross examination. Detection of the type of GB neoplasm and reporting the depth of invasion are important for appropriate management. Histopathologic examination of all cholecystectomy specimens is a must, even if no malignancy is detected radiologically or grossly. We describe a series of eight incidentally detected GB neoplasms and discuss the morphological features, staging, and management along with clinical significance.